PENGARUH MOTIVASI, METODE PEMBELAJARAN DAN DISIPLIN BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA TEKNIK DI POLITEKNIK NEGERI SRIWIJAYA (Studi Penelitian pada Mahasiswa Jurusan Teknik Kimia) - Ibnu Maja (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2013)
The low achievement of students and the lack of motivation, methods of learning and discipline in the students' learning of mathematics is a challenge for mathematics lecturers to continue to think creatively in order to teach the material to students in accordance with the standards of the curriculum and the learning process takes place by directly involving students in full in terms of the learning process that takes place can be run with fun. The low achievement of students was indirectly caused by the lack of students' motivation and discipline itself. Learning methods implemented by the faculty also affects the achievement of students majoring in chemical engineering. The learning method is a technique applied by teachers in the learning process, because the learning process is a process of knowledge transfer from faculty as a lecturer to the students as learners and for that there must be a special technique to be effective and well targeted. If the teaching methods employed by teachers precisely, the maximum learning outcomes clear and satisfactory.